Protective Role of High-Density Lipoprotein in Multiple Sclerosis - Agnieszka Damiza-Detmer; Małgorzata Pawełczyk; Andrzej Głąbiński (MDPI AG, 2024)
Multiple sclerosis (MS) is a chronic, progressive demyelinating disease with a most likely autoimmune background and a neurodegenerative component. Besides the demyelinating process caused by autoreactive antibodies, an increased permeability in the blood-brain barrier (BBB) also plays a key role. Recently, there has been growing interest in assessing lipid profile alterations in patients with MS. As a result of myelin destruction, there is an increase in the level of cholesterol released from cells, which in turn causes disruptions in lipid metabolism homeostasis both in the central nervous system (CNS) and peripheral tissues. Currently, there is a growing body of evidence suggesting a protective role of HDL in MS through its effect on the BBB by decreasing its permeability. This follows from the impact of HDL on the endothelium and its anti-inflammatory effect, mostly by interacting with adhesion molecules like vascular cell adhesion molecule 1 (VCAM-1), intercellular adhesion molecule 1 (ICAM-1), and E-selectin. HDL, through its action via sphingosine-1-phosphate, exerts an inhibitory effect on leukocyte migration, and its antioxidant properties contribute to the improvement of the BBB function. In this review, we want to summarize these studies and focus on HDL as a mediator of the anti-inflammatory response in MS.